2021
DOI: 10.14202/vetworld.2021.2714-2718
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acetate containing fluid versus lactate containing fluid on acid-base status, electrolyte level, and blood lactate level in dehydrated dogs

Abstract: Background and Aim: Acetate or lactate buffered, balanced isotonic rehydration fluids are commonly used for fluid therapy in dogs and may influence acid-base and electrolyte status. This study aimed to assess acid-base status, electrolyte levels, and lactate levels in dehydrated dogs after receiving acetate or lactate-containing intravenous rehydration fluids. Materials and Methods: In this prospective, randomized study, 90 dehydrated dogs were included and randomized to receive acetate [Sterofundin® ISO B. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…Overall, both fluid types seem to have a similarly low impact on the patients' acid-base status, when given as an intravenous bolus of 30 mL/kg. This is in accordance with another study in dehydrated dogs, which also found no significant difference in acid-base parameters between the two fluids, when administered over a period of 6 to 24 h for rehydration (41). According to a meta-analysis of 29 studies comparing acetate-and lactate-containing fluids, the results concerning the acid-base status were conflicting.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Overall, both fluid types seem to have a similarly low impact on the patients' acid-base status, when given as an intravenous bolus of 30 mL/kg. This is in accordance with another study in dehydrated dogs, which also found no significant difference in acid-base parameters between the two fluids, when administered over a period of 6 to 24 h for rehydration (41). According to a meta-analysis of 29 studies comparing acetate-and lactate-containing fluids, the results concerning the acid-base status were conflicting.…”
Section: Discussionsupporting
confidence: 86%
“…In another study, dehydrated dogs were resuscitated with either a lactate-containing, or an acetate-containing solution. The total fluid volume administered depended on the individual patients' requirements, but the median volume was > 100 mL/kg, administered over 6 to 24 h. Plasma lactate levels decreased significantly in both groups, but the decrease was more pronounced in the acetate-group (41). A study in people undergoing major surgeries found higher intraoperative lactate levels in patients receiving 10 mL/kg/h of a lactate-containing solution, compared with the same rate of an acetate-containing solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation